2010
DOI: 10.3141/2164-06
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Environmental Effectiveness of Titanium Dioxide Photocatalyst Coating for Concrete Pavement

Abstract: Self-cleaning, air-purifying concrete pavement is a rapidly emerging technology that can be constructed with air-cleaning agents with a super-hydrophilic photocatalyst such as titanium dioxide (TiO2). Although this technology has the potential to support an environmentally friendly road infrastructure, several design and operational parameters may affect its effectiveness and need to be evaluated. The objective of this study was to evaluate the environmental and mix design parameters that may affect the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 13 publications
5
37
0
Order By: Relevance
“…It has been assumed that at higher relative humidity water molecules compete with pollutant molecules for adsorption sites at the material A c c e p t e d M a n u s c r i p t 18 surface, which would explain the decrease in pollutant removal (Hüsken et al, 2009;Laufs et al, 2010;Maggos et al, 2007b;Ao et al, 2003). Dylla et al (Dylla et al, 2010) also observed an increase in removal with higher contact times as observed in this study (Figure 4a). Increasing contact time increases the probability of pollutants coming in contact with the material surface and being adsorbed and reacted, hence the positive contrast for that factor.…”
Section: Discussion Nitrogen Oxide Removal Main Effectssupporting
confidence: 69%
See 3 more Smart Citations
“…It has been assumed that at higher relative humidity water molecules compete with pollutant molecules for adsorption sites at the material A c c e p t e d M a n u s c r i p t 18 surface, which would explain the decrease in pollutant removal (Hüsken et al, 2009;Laufs et al, 2010;Maggos et al, 2007b;Ao et al, 2003). Dylla et al (Dylla et al, 2010) also observed an increase in removal with higher contact times as observed in this study (Figure 4a). Increasing contact time increases the probability of pollutants coming in contact with the material surface and being adsorbed and reacted, hence the positive contrast for that factor.…”
Section: Discussion Nitrogen Oxide Removal Main Effectssupporting
confidence: 69%
“…It should be noted, however, that the other studies used higher inlet concentrations (300 ppb and over) than this study (150 ppb). For example, Dylla et al (Dylla et al, 2010) observed NO removals in the 20 to 60% range for contact time varying from 2.4 to 7.1 minutes.…”
Section: Discussion Nitrogen Oxide Removal Main Effectsmentioning
confidence: 96%
See 2 more Smart Citations
“…Furthermore, mechanical properties of concrete are adversely affected by increasing concentrations of TiO 2 [32]. Other laboratory experiments have employed double layer blocks [17] [33], with only the upper layer having the photocatalyst in relatively high proportions. This preparation, requiring two steps, would ultimately result in increased production costs and some technical inconveniences such as blockage of the porous structure in the concrete and delamination of the photoactive facade.…”
Section: Introductionmentioning
confidence: 98%